Determination of Climate Factors in Flood and Drought Disaster in Indonesia using Instrumental Variable (IV) Methods - Faradiba Faradiba (Jurnal Ilmu Fisika, 2021)
Located in the Southeast Asia region, Indonesia has rainy and dry seasons. In the rainy and dry seasons that occur in Indonesia, often causes many problems in various business sectors and community activities, including floods and droughts. It is known that the disaster will have an impact on material and non-material losses. This study uses climate data and disaster data at the village level to determine the effect of rainfall on disasters. This study uses the instrumental variable method because the model has endogeneity problems. The study results concluded that increased rainfall had a positive impact on flood disasters with a coefficient of 0.003038. Simultaneously, rainfall also impacted drought with a coefficient of -0.000377.Â  Variables in the regression model that are formed can explain 1.74 percent of the flood disaster and 0.59 percent of the drought disaster. These results indicate that most of the other variables can influence flooding and drought. Through this research, it is known that rainfall for floods and droughts is quite significant. Therefore, government and community efforts are needed to anticipate similar disasters.